Himhemisphären - Textstrukturen - Grammatikerkenntnis - GÖTZE, Lutz (Wydawcnictwo Naukowe UAM, 1994)
In this article some of the new results of research in cerebral hemispheres are interpreted in order to get information about second language teaching and learning. Those factors are mentioned which enable foreign learners to read and to understand sentences and texts. On the other hand we now know something more about how grammatical rules could be understood. Nevertheless, there are still more questions than answers, especially about the problem whether our brain contains several specified areas (language centre etc.) or the brain is merely a neuronal system of networks. Further research is demanded urgently.